Perangkat Lunak Pengelolaan Surat Di Kecamatan Lengkong - Deden Sofyan Hamdani (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2020)
The development of a country makes it easier for its people to obtain information. This is obvious from the apparent increasing needs of the community, companies and government institutions in obtaining various data and information. The District Office of Lengkong, Bandung City is one of the government institutions which, in running its governmental functions, requires a well-computerized information system. The information system needed is an information system that can handle the processing and delivery of information and data related to letters received and sent. The software used is a desktop-based application which makes it easier to maintain the archieves in Lengkong District Office. To design a desktop, a designing stage is required using a prototype model, and the tool used to design the desktop is Star UML. The programming language used to make this desktop is the Visual Basic programming language, and the database is MySQL. It can be concluded that the Letters Management Software in the Lengkong District makes it easier for all employees to maintain records in the institution and in accessing the needed archives.